2014
DOI: 10.1287/opre.2014.1289
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Near-Optimal Algorithm for Online Linear Programming

Abstract: A natural optimization model that formulates many online resource allocation and revenue management problems is the online linear program (LP) where the constraint matrix is revealed column by column along with the objective function. We provide a near-optimal algorithm for this surprisingly general class of online problems under the assumption of random order of arrival and some mild conditions on the size of the LP right-hand-side input. Our learning-based algorithm works by dynamically updating a threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
250
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(261 citation statements)
references
References 32 publications
6
250
0
3
Order By: Relevance
“…Roughly speaking, in [6] (and similarly in other work [7,25,1], it is shown that as long as the sample is of size ≈ n, the overall assignment will be ≈ close to the optimal offline solution.…”
Section: Comparison To the Primal-dual Methodsmentioning
confidence: 96%
See 4 more Smart Citations
“…Roughly speaking, in [6] (and similarly in other work [7,25,1], it is shown that as long as the sample is of size ≈ n, the overall assignment will be ≈ close to the optimal offline solution.…”
Section: Comparison To the Primal-dual Methodsmentioning
confidence: 96%
“…Our work is closely related to online ad allocation problems, including the Display Ads Allocation (DA) problem [8,7,1,25], and the AdWords (AW) problem [16,6]. In both of these problems, the publisher must assign online impressions to an inventory of ads, optimizing efficiency or revenue of the allocation while re- [6].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations